2014
DOI: 10.1063/1.4890829
|View full text |Cite
|
Sign up to set email alerts
|

Numerical nonlinear analysis of subcritical Rayleigh-Bénard convection in a horizontal confined enclosure filled with non-Newtonian fluids

Abstract: A computational model for the dynamic stabilization of Rayleigh-Bénard convection in a cubic cavity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 37 publications
5
33
1
Order By: Relevance
“…Benouared et al [12] found a subcritical Rayleigh number R sc ¼ 800, whereas our computations show that 780 < R sc < 782:5, which is only 2% smaller. Moreover, the value of Nusselt number at R ¼ 800 found by [12] is Nu ¼ 1:4798 to compare to our value, Nu ¼ 1:4751: the relative difference is smaller than 0:32%. A second point was compared at R ¼ 2000, and the relative difference of the Nusselt numbers is 0:38% (Nu ¼ 2:7759 for [12] and Nu ¼ 2:7655 for us).…”
Section: Analysis With An Effective Viscosity -Relevance Of the Averacontrasting
confidence: 68%
See 4 more Smart Citations
“…Benouared et al [12] found a subcritical Rayleigh number R sc ¼ 800, whereas our computations show that 780 < R sc < 782:5, which is only 2% smaller. Moreover, the value of Nusselt number at R ¼ 800 found by [12] is Nu ¼ 1:4798 to compare to our value, Nu ¼ 1:4751: the relative difference is smaller than 0:32%. A second point was compared at R ¼ 2000, and the relative difference of the Nusselt numbers is 0:38% (Nu ¼ 2:7759 for [12] and Nu ¼ 2:7655 for us).…”
Section: Analysis With An Effective Viscosity -Relevance Of the Averacontrasting
confidence: 68%
“…To validate our numerical method when g 1 -0, we compare with [12] for P ¼ 10; n i ¼ 0:6; k ¼ 0:4; g 1 ¼ 0:01, and for an aspect ratio of the cell L x =d ¼ 1, which would not bring significantly different results than with our value L x =d ¼ 1:008. Benouared et al [12] found a subcritical Rayleigh number R sc ¼ 800, whereas our computations show that 780 < R sc < 782:5, which is only 2% smaller.…”
Section: Analysis With An Effective Viscosity -Relevance Of the Averamentioning
confidence: 94%
See 3 more Smart Citations